Integrating ChatGPT in EFL writing: Perceptions and challenges of Islamic senior high school students - Bunayya Izzani Fathi Musaqqaf; Maslihatul Bisriyah (Journal of English Language Teaching and Learning (JETLE), 2026)
The increasing integration of artificial intelligence tools such as ChatGPT in EFL writing has raised interest in how students experience the use of these tools in learning. This study aims to explore students’ experiences of using ChatGPT and to identify the challenges they encountered. Employing a qualitative phenomenological design, the study involved 23 students from eight working groups. Data were collected through classroom observations during writing activities and semi-structured interviews with six students representing different academic levels. The findings indicate that students generally perceive ChatGPT as a supportive tool that facilitates idea generation, improves sentence organization, and enhances language use. Many students reported increased confidence in writing when using ChatGPT as a reference and scaffolding resource. However, several challenges were also identified, including technical issues such as unstable internet access and cognitive challenges such as limited prompt literacy, overreliance on AI-generated responses, reduced creativity, and diminished critical thinking. Students with higher motivation and stronger language proficiency demonstrated more critical and selective use of ChatGPT, while others tended to depend on it as a shortcut. This study highlights that the effectiveness of ChatGPT depends not only on technological access but also on students’ readiness and teacher guidance to promote critical, ethical, and reflective use.